2010
DOI: 10.1099/vir.0.027490-0
|View full text |Cite
|
Sign up to set email alerts
|

The GB viruses: a review and proposed classification of GBV-A, GBV-C (HGV), and GBV-D in genus Pegivirus within the family Flaviviridae

Abstract: In 1967, it was reported that experimental inoculation of serum from a surgeon (G.B.) with acute hepatitis into tamarins resulted in hepatitis. In 1995, two new members of the family Flaviviridae, named GBV-A and GBV-B, were identified in tamarins that developed hepatitis following inoculation with the 11th GB passage. Neither virus infects humans, and a number of GBV-A variants were identified in wild New World monkeys that were captured. Subsequently, a related human virus was identified [named GBV-C or hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
327
0
20

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(360 citation statements)
references
References 125 publications
8
327
0
20
Order By: Relevance
“…The human liver-chimeric mouse models and genetically engineered mice are useful for some studies, but lack functional immune systems or allow only limited viral replication (31). GBV-B infection of New World monkeys has been used as a surrogate model, but persistent infection is rare (12,31). Despite recent breakthroughs in HCV therapy (28), vaccine efforts lag far behind and would be aided by a better understanding of hepacivirus immunity and a preclinical model for testing vaccine candidate concepts (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human liver-chimeric mouse models and genetically engineered mice are useful for some studies, but lack functional immune systems or allow only limited viral replication (31). GBV-B infection of New World monkeys has been used as a surrogate model, but persistent infection is rare (12,31). Despite recent breakthroughs in HCV therapy (28), vaccine efforts lag far behind and would be aided by a better understanding of hepacivirus immunity and a preclinical model for testing vaccine candidate concepts (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, hepaciviruses have also been discovered in rodents (6,9), bats (10), and Old World primates (11). Pegiviruses are closely related to hepaciviruses and include human (HPgV/ GBV-C) and simian (SPgV/GBV-A) pegiviruses, none of which are associated with disease (12). More recently, rodent (RPgV) (9), bat (BPgV) (10), and equine (EPgV and Theiler's disease associated virus, TDAV) (13,14) pegiviruses were discovered.…”
mentioning
confidence: 99%
“…Exosomes are microvesicles of endocytic origin that are emerging as novel particles employed by cells and viruses to transmit viral and cellular RNAs and proteins to cells (Meckes & Raab-Traub, 2011). As HPgV and other members of the genus Pegivirus do not appear to encode a nucleocapsid protein at the N terminus of the polyprotein (Xiang et al, 1998;Stapleton et al, 2011), cellular-derived microvesicles (which carry~50 % of the HPgV RNA found in plasma; Bhattarai et al, 2013) may be involved in virus release and/ or cellular infection. Supporting this hypothesis, HPgV RNA-containing microvesicles positive for an exosomal marker (cellular CD63) were able to deliver viral RNA to uninfected PBMCs and viral RNA replicated within these cells ex vivo (Chivero et al, 2014).…”
Section: Life Cyclementioning
confidence: 99%
“…Given precedent with other blood-borne pathogens like HIV and hepatitis B virus, efforts to find homologs of HCV have focused on nonhuman primates. To date, these efforts have been unsuccessful (14). Dogs were domesticated as early as 8,000 BCE (16) and, as companion and working animals, occupy a unique niche at the human-animal interface.…”
mentioning
confidence: 99%
“…Since its discovery about 20 y ago (11,12), the origin of hepatitis C virus (HCV) remains obscure largely because a closely related animal virus homolog has not been identified (13,14). Worldwide, 200 million people are chronically infected with HCV (13,15) and are at risk for developing liver fibrosis, cirrhosis, and hepatocellular carcinoma.…”
mentioning
confidence: 99%